2016
DOI: 10.3390/md14070123
|View full text |Cite
|
Sign up to set email alerts
|

Structural Features and Potent Antidepressant Effects of Total Sterols and β-sitosterol Extracted from Sargassum horneri

Abstract: The purified total sterols and β-sitosterol extracted from Sargassum horneri were evaluated for their antidepressant-like activity using the forced swim test (FST) and tail suspension test (TST) in mice. Total sterols and β-sitosterol significantly reduced the immobility time in the FST and TST. Total sterols were administered orally for 7 days at doses of 50, 100, and 200 mg/kg, and β-sitosterol was administered intraperitoneally at doses of 10, 20, and 30 mg/kg. β-sitosterol had no effect on locomotor activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 41 publications
1
40
0
Order By: Relevance
“…In that case, 30 mg/kg exerted effects similar to those of 20 mg/kg of fluoxetine on FST and TST. Finally, the effects on monoamine levels in mice brains confirm that sterols modify the serotonergic and noradrenergic systems but do not impact the dopaminergic system [93].…”
Section: Sterols With Anxiolytic and Antidepressant Effectsmentioning
confidence: 66%
“…In that case, 30 mg/kg exerted effects similar to those of 20 mg/kg of fluoxetine on FST and TST. Finally, the effects on monoamine levels in mice brains confirm that sterols modify the serotonergic and noradrenergic systems but do not impact the dopaminergic system [93].…”
Section: Sterols With Anxiolytic and Antidepressant Effectsmentioning
confidence: 66%
“…Chronic treatment with the ethanol extract (50, 100, and 200 mg/kg) did not significantly inhibit brain MAO-A activity in both unstressed and stressed mice, indicating that MAO-A inhibition might not be responsible for antidepressant activity of the ethanol extract. Further, antidepressant activity of the extract might be due to the presence of beta-sitosterol, which is present in the extract to the extent of 3.68%, since antidepressant activity of beta-sitosterol has been reported in the literature [42].…”
Section: Discussionmentioning
confidence: 97%
“…In the present investigation, ethanol extract of flowers of T. undulata administered for 21 successive days showed significant antidepressantlike activity in mice subjected to CUMS. Induction of depression using CUMS is considered as the most valid animal model of depressive behavior observed in humans after long-term exposure to multiple stressors [42,43]. CUMS-induced depression model can be used for evaluating the potential antidepressants by employing behavioral tests such as TST [32] and sucrose preference test [9].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies reported neuroprotective role of astaxanthin and fucoxanthin [145, [282][283][284][285][286][287], Sargassum spp. [288][289][290][291][292][293][294][295], Saccorhiza polyschide [283], Codium tomentosum [296], Ulva spp [256,267,293,[297][298][299][300], Ecklonia maxima [256,[301][302][303], Gracilaria spp. (Figure 12) [296,[304][305][306][307][308][309][310][311], Gelidium pristoides [312,313], Halimeda incrassate [314,315], Bryothamniom triquetrum [316][317][318], Chondrus crispus ( Figure 13) [319,320], Hypnea valentiae (…”
Section: Neuroprotection In Stroke Alzheimer's and Parkinsonismmentioning
confidence: 99%